PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI DAN KOMPENSASI NON FINANSIAL TERHADAP KINERJA PEGAWAI (Studi Kasus pada Sekretariat Direktorat Jenderal Imigrasi) - Fitriani, Dede (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2021)
The purpose of this study is to examine the effect of transformational leadership, organizational culture, and non-financial compensation on the performance of Setditjenim employees. Types of Quantitative Research, research population of all employees of non structural setditjenim 138 people with probability sampling technique with sample random sampling The research method using Multiple Linear Regression Analysis and data processed using statistical methods using SPSS 24.0 For Windows. The results showed that transformational leadership had no significant effect on performance, organizational culture, and non financial compensation had no significant effect on performance, and transformational leadership, organizational culture and non financial compensation together significantly influenced the performance of the Secretariat staff of the Directorate General of Immigration. Secretariat of the Directorate General of Immigration to continue to develop organizational culture to improve employee performance.